2018
DOI: 10.1021/acs.jafc.8b00333
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Air, Oxygen, Nitrogen, and Carbon Dioxide Nanobubbles on Seed Germination and Plant Growth

Abstract: Nanobubbles (NBs) hold promise in green and sustainable engineering applications in diverse fields (e.g., water/wastewater treatment, food processing, medical applications, and agriculture). This study investigated the effects of four types of NBs on seed germination and plant growth. Air, oxygen, nitrogen, and carbon dioxide NBs were generated and dispersed in tap water. Different plants, including lettuce, carrot, fava bean, and tomato, were used in germination and growth tests. The seeds in water-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 46 publications
1
71
1
2
Order By: Relevance
“…Therefore, hypoxic stress (situations in which the oxygen concentration is a limiting factor) might not occur in this soil and further injection of air into the soil through irrigation showed no effect on plant growth. This result differed with the study of Ahmed et al [29], who observed that air nano-bubbled into water not only had a negative effect on tomato growth also appeared to slow down the growth rates of the hypocotyl length compared to tap water. Li et al [30] reported that, once aeration had eliminated hypoxic stress, more air injected resulted in a reduction in root to soil contact which had a negative effect on the rhizosphere, and decreased tomato fruit yields.…”
Section: Aerated Irrigation and Biochar On Yield And Ion Uptake Of Kocontrasting
confidence: 99%
“…Therefore, hypoxic stress (situations in which the oxygen concentration is a limiting factor) might not occur in this soil and further injection of air into the soil through irrigation showed no effect on plant growth. This result differed with the study of Ahmed et al [29], who observed that air nano-bubbled into water not only had a negative effect on tomato growth also appeared to slow down the growth rates of the hypocotyl length compared to tap water. Li et al [30] reported that, once aeration had eliminated hypoxic stress, more air injected resulted in a reduction in root to soil contact which had a negative effect on the rhizosphere, and decreased tomato fruit yields.…”
Section: Aerated Irrigation and Biochar On Yield And Ion Uptake Of Kocontrasting
confidence: 99%
“…19 In summary, the studies of micro/ nanoaerated drip irrigation have been only focus on improving crop yield and quality, 13 promoting crop seed germination, and reducing environmental damage in the process of fertilizer production and use to date. 20 Few studies have focused on the inuence of micro/nanobubbles on the process of drip irrigation system clogging; these studies are still at the initial stage. However, in the actual crop production process, emitter clogging seriously restricts the performance, service life, and popularization of drip irrigation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we can reasonably assume that most NO is produced from O 2 in O 2 /N 2 nanobubbles. These are known to provide oxidants and reductants which might interact with arginine extracellularly to produce NO (Hickok et al ., 2013; Liu et al ., 2016; Ahmed et al ., 2018). More blood flow would tend to bring in more O 2 nanobubbles, and hence explain the correlation between increased flow, NO and vasodilation.…”
Section: The Esl Nanobubble Model Explains Paradoxes and Anomaliesmentioning
confidence: 99%